2019
DOI: 10.1002/anie.201905142
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of a Tetrafluoroterephthalonitrile‐β‐Cyclodextrin Polymer to Remove Anionic Micropollutants and Perfluorinated Alkyl Substances from Water

Abstract: Organic micropollutants (MPs) are anthropogenic substances that contaminate water resources at trace concentrations.M any MPs,i ncluding per-a nd polyfluorinated alkyl substances (PFASs), have come under increased scrutiny because of their environmental persistence and association with various health problems.Ab-cyclodextrin polymer linked with tetrafluoroterephthalonitrile (TFN-CDP) has high affinity for cationic and many neutral MPs from contaminated water because of anionic groups incorporated during the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
119
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(123 citation statements)
references
References 32 publications
2
119
0
2
Order By: Relevance
“…Lately, to improve the adsorption performance of anionic micropollutants and perfluorinated alkyl substances from water, primary amines were preset in the tetrafluoroterephthalonitrile linked β-CD polymer, which wiped 80-98% of all contaminants within 30 min. [143] Based on the background in both porous polymers and environment control, the COF-based materials for adsorption have also been reported by Dichtel's group. A highly porous (≥1000 m 2 g −1 ) imine-linked 2D COFs bearing primary amines was employed to rapidly adsorb ammonium perfluoro-2-propoxypropionate (GenX) and other PFASs (Figure 5a).…”
Section: Nitrile Reductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lately, to improve the adsorption performance of anionic micropollutants and perfluorinated alkyl substances from water, primary amines were preset in the tetrafluoroterephthalonitrile linked β-CD polymer, which wiped 80-98% of all contaminants within 30 min. [143] Based on the background in both porous polymers and environment control, the COF-based materials for adsorption have also been reported by Dichtel's group. A highly porous (≥1000 m 2 g −1 ) imine-linked 2D COFs bearing primary amines was employed to rapidly adsorb ammonium perfluoro-2-propoxypropionate (GenX) and other PFASs (Figure 5a).…”
Section: Nitrile Reductionmentioning
confidence: 98%
“…Anionic micropollutant and PFASs [143] Amine-modified PIM-1 -Amines Amidation and nitrile reduction Selective-dye adsorption [144] Z-PAF-C -Zwitterions Ring opening reaction Antifouling salt rejection membrane [145] PAF [TEMPO]50%-NiP-COF 264 TEMPO "click" reaction Supercapacitor [142] S-CTF-1 -Sulfur Vulcanization LSB [160] S-COF-V 6 Sulfur Vulcanization LSB [161] polysulfide@ TFPPy-ETTA-COF -Sulfur Vulcanization LSB [162] CEA ( Figure 3c). The stretching/shrinking of PDMAEMA chains in different pH conditions can manipulate the aggregation state of CEA indicators, enabling the visible pH-sensitive fluorescence change.…”
Section: Nitrile Reductionmentioning
confidence: 99%
“…57 In very recent work, they demonstrated that the reduction of the -CN group into -CH 2 NH 2 dramatically enhances the affinity of the material for PFOA. 58 Work on tailoring porous organic materials to capture water contaminants has recently been reviewed. 59…”
Section: Covalent Organic Framework and Porous Organic Polymersmentioning
confidence: 99%
“…[9c, 11] Macrocycles are at the heart of solutions to societally important problemsi ncluding the formulation of insoluble drugs, [6] the household product Febreeze TM , [12] glucose monitors, [13] sequestrants for nuclear waste ions, [14] and the removal of contaminants from water sources. [15] Amongst thesem olecular containers, cucurbit[n]urils (CB[n], Figure 1) [16] have distin-guishedt hemselves due to their ability to form high affinity CB [n]•guest complexesi nh ighly selective and stimuli responsive processes in aqueous solution. [17] Accordingly,m acrocyclic CB[n]a nd their derivatives have been extensivelyi nvestigated as componentso fs ensing ensembles, [18] molecular machines, [19] in pharmaceutical applications, [20] as catalysts, [21] and are even beginning to appear in commercial deodorizing products.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most popular classes of macrocyclic receptors include the crown ethers, [1c] cryptands, [1b] cyclodextrins, [6] calixarenes, [7] cyclophanes, [1a, 3a, 8] cavitands, [9] pillararenes, [10] as well as cages self‐assembled by H‐bonding, the hydrophobic effect, and metal–ligand interactions [9c, 11] . Macrocycles are at the heart of solutions to societally important problems including the formulation of insoluble drugs, [6] the household product Febreeze TM , [12] glucose monitors, [13] sequestrants for nuclear waste ions, [14] and the removal of contaminants from water sources [15] . Amongst these molecular containers, cucurbit[ n ]urils (CB[ n ], Figure 1) [16] have distinguished themselves due to their ability to form high affinity CB[ n ]⋅guest complexes in highly selective and stimuli responsive processes in aqueous solution [17] .…”
Section: Introductionmentioning
confidence: 99%